Knowledge Cartography for Open Sensemaking Communities - Simon Buckingham Shum (Journal of Interactive Media in Education, 2008)
Knowledge Cartography is the discipline of visually mapping the conceptual structure of ideas, such as the connections between issues, concepts, answers, arguments and evidence. The cognitive process of externalising one's understanding clarifies one's own grasp of the situation, as well as communicating it to others as a network that invites their contributions. This sensemaking activity lies at the heart of the Open Educational Resources movement's objectives. The aim of this paper is to describe the usage patterns of Compendium, a knowledge mapping tool from the OpenLearn OER project, using quantitative data from interaction logs and qualitative data from knowledge maps, forums and blog postings. This work explains nine roles played by maps in OpenLearn, and discusses some of the benefits and adoption obstacles, which motivate our ongoing work.Editors: Patrick McAndrew (Open University, UK)Reviewers: Hendrik Drachsler (Open University, NL) and Patrick McAndrew (Open University, UK).Interactive elements: Examples and downloads for the Compendium software can be found on the OpenLearn site http:/www.open.ac.uk/openlearn